Are there differences in risk factors, microbial aspects, and prognosis of cellulitis between compensated and decompensated hepatitis C virus-related cirrhosis? - Elham Ahmed Hassan; Abeer Sharaf El-Din Abdel Rehim; Mohamed Omar Abdel-Malek; Asmaa Omar Ahmed; Nourhan Mahmoud Abbas (Clinical and Molecular Hepatology, 2019)
Background/Aims Cellulitis is a common infection in patients with liver cirrhosis. We aimed to compare risk factors, microbial aspects, and outcomes of cellulitis in compensated and decompensated hepatitis C virus (HCV)-related cirrhosis. Methods Six hundred twenty consecutive HCV-related cirrhotic patients were evaluated for cellulitis. Demographic and clinical data were evaluated, along with blood and skin cultures. Severity of cirrhosis was assessed using Child-Pugh score. In-hospital mortality was assessed. Results Seventy-seven (12.4%) cirrhotic patients had cellulitis (25 with compensated and 52 with decompensated disease). Smoking and venous insufficiency were risk factors of cellulitis in compensated cirrhosis. Leg edema, ascites, hyperbilrubinemia and hypoalbuminemia were risk factors in decompensated cirrhosis. Gram-positive bacteria (Staphylococcus spp. and Streptococcus pyogenes) were the infective organisms in compensated patients, while gram negative bacteria (Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa) were the predominant organisms in decompensated cirrhosis. Fungi (Candida albicans and Aspergillus niger) were detected in 3 decompensated cases. In-hospital mortality in patients with cellulitis was 27.3%, approaching 100% in decompensated patients with gram-negative cellulitis. Prolonged hospitalization, higher model for end-stage liver disease (MELD)-Na score, septic shock, local complication, and recurrent cellulitis were predictors of mortality. Conclusions Cellulitis in compensated cirrhosis is different from that of decompensated patients regarding microorganisms, pathogenesis, and prognosis. Cellulitis has a poor prognosis, with mortality rates approaching 100% in decompensated patients with gram-negative cellulitis. Stratifying patients according to severity of cirrhosis is important to identify the proper empirical antibiotic and to decide the proper means of care.